2019
DOI: 10.1021/acs.chemrev.9b00232
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire Photoelectrochemistry

Abstract: Recent applications of photoelectrochemistry at the semiconductor/ liquid interface provide a renewable route of mimicking natural photosynthesis and yielding chemicals from sunlight, water, and air. Nanowires, defined as one-dimensional nanostructures, exhibit multiple unique features for photoelectrochemical applications and promise better performance as compared to their bulk counterparts. This article reviews the use of semiconductor nanowires in photoelectrochemistry. After introducing fundamental concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
140
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 285 publications
0
140
0
Order By: Relevance
“…The GaN/n + -p Si platform takes advantage of the strong light-harvesting of Si (bandgap of 1.1 eV) and efficient electron extraction/transportation effect as well as large surface area provided by GaN nanowires ( Vanka et al., 2018 ; Zhou et al., 2018 ). The nanowires allow high mass loadings of electrocatalyst and enhance the light absorption with decreased light reflection ( Deng et al., 2019a ). Significantly, the optical absorption and electrochemical reaction are decoupled spatially and functionally in the multi-dimensional structure, providing a unique platform to tune the product distribution by simply varying the cocatalyst composition.…”
Section: Resultsmentioning
confidence: 99%
“…The GaN/n + -p Si platform takes advantage of the strong light-harvesting of Si (bandgap of 1.1 eV) and efficient electron extraction/transportation effect as well as large surface area provided by GaN nanowires ( Vanka et al., 2018 ; Zhou et al., 2018 ). The nanowires allow high mass loadings of electrocatalyst and enhance the light absorption with decreased light reflection ( Deng et al., 2019a ). Significantly, the optical absorption and electrochemical reaction are decoupled spatially and functionally in the multi-dimensional structure, providing a unique platform to tune the product distribution by simply varying the cocatalyst composition.…”
Section: Resultsmentioning
confidence: 99%
“…It is also observed that the absorption capacity of CdS samples increases with the length of nanorods beyond 550 nm and among them the C-18 sample shows the highest absorption features up to near-infrared (NIR) regions. This phenomenon is attributed to the light scattering effect of 1D nanomaterials [51,52]. Usually the photocatalytic activity is determined by the light harvesting capability.…”
Section: Uv-vis Absorption Bandgap and Bandstructure Studiesmentioning
confidence: 99%
“…The interface of heterogeneous catalysis plays a key role in catalytic reactions, and the catalytic path is governed by controlling the atomic and electronic structure of interface. Thus, tuning the interface of nanoparticles provides a versatile route for optimization of heterogeneous catalysts, [1][2][3][4][5][6][7][8] and interface design is one of the most significant and promising motivations to boost the electrochemical reactions. [9] Hydrogen has the highest gravimetric energy density among all the chemical fuels, [10] and is thus hailed as the ultimate clean energy carrier.…”
Section: Introductionmentioning
confidence: 99%